Microwave-Accelerated Synthesis of Flavanones through Oxidative Cyclization of 2'-Hydroxychalcones Using Acetic Acid as a Sole Catalyst - Bajracharya, Gan B.; Dhakal, Rabina; Timalsina, Sulochana (Journal of Nepal Chemical Society, 2024)
Under microwave irradiation conditions, 2'-hydroxy chalcones 1a-c underwent AcOH-mediated cyclization in an oxa-Michael addition manner to afford flavanones 2a-c in acceptable yields (up to 82%). These reactions proceeded in a shorter reaction time (~ 30 min) through microwave activation; otherwise, the reaction would take several days and even weeks, if a conventional heating process was employed. For example, cyclization of (E)-1-(2-hydroxyphenyl)-3-phenylprop-2-en-1-one (1a) has required 4 days of stirring with AcOH (0.25 M), under conventional heating at 100 °C, to produce 2-phenylchroman-4-one (2a), in 75% yield; while under microwave conditions, the reaction has yielded 82% of compound 2a, after 30 min. Thus obtained products 2a-c were fully characterized by recording of melting point together with UV, 1H NMR, and 13C NMR spectra.